Monitoring of national projects in Russia and risks associated with their implementation - V. V. Stroev; N. V. Kuznetsov (Вестник университета)
National projects developed in accordance with the national development goals of Russia allow us to implement key tasks for socio-economic development of the country, as well as welfare of its population. Evaluation of performance indicators and control points at all stages of national projects functioning allows to determine the need for operational management decisions at local, regional, and federal levels. In the conducted research, the monitoring implementation of national projects in Russian system has been considered. The assessment of key risks and possible threats to national projects implementation has been performed out, as well as possible ways to solve problems proposed. The main documents that regulate national projects execution, the mechanism and structure of national projects monitoring have also been studied. Traditional theoretical research methods were used in the article, including system analysis and synthesis, as well as inductive and deductive approaches that made it possible to evaluate the “Electronic Budget” – a unified state integrated information system for public finance management of Russia, as well as a separately functioning system based on the “Center for Information Technology and Systems of Executive Authorities named after A.V. Starovoitov” called “Information system for monitoring national projects and programmes in the social sphere”. The analysis results obtained allowed us to conclude the key problems and errors in the process of monitoring national projects implementation in Russia and to make suggestions for their elimination.